LINGUOCULTUROLOGICAL ANALYSIS OF THE SEMANTIC FEATURES OF PHRASEOLOGICAL UNITS - Tamara Kavilova; Yulduz Abdurazzoqova (Journals Park Publishing, 2022)
The comparative analysis of phraseological expressions of Russian and English languages with semantic components made it possible to clearly imagine how diverse they are in their semantics and expressiveness.The theoretical analysis showed that a phraseological unit is a vivid figurative expression with a rethought semantics of its components, the originality of which is based on various grammatical, lexical, semantic dependencies between them, and the specificity of phraseological meaning is determined by the properties of words - lexical components of a phraseological unit, and internal phraseological connections.
Keywords: phraseological units; structural-semantic; analysis, significative-denotative component